Common Infectious Diseases Among the Hospitalized Elderly Patients - Mansooreh Momen Heravi; Hasan Afzali; Zahra Soleimani; Moin Matin (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The elderly are more susceptible to the infectious diseaseswith higher risk of morbidity and mortality. Variouspresentations of infectious disease in the elderly can lead to delay in diagnosis. This study aimed to evaluate the clinical featuresof infectious diseases and laboratory findings among the hospitalized elderly patients. Methods & Materials: In a cross sectional study, 248 older people admitted to Beheshti hospital of kashan, Iran, during the year 2009, with an infectious disease were recruited. The patient was diagnosed with an infection if fever or a local site of infection was present. After history taking and physical examination, laboratory tests including blood culture, urine culture, CBC, ESR, and CRP and diagnostic imagings such as sonography, CT scan and MRI were performed. Demographic information, clinical findings and laboratory tests results were recorded through interviews, as well as review of medical records. The results are presented by descriptive statistics. Results: Among a total of 248 patients with mean age of 74. 3 years old, 133(53.6%) were male. Most of the patients (78.4%) aged 60-75 years old. The most common chief complaint was fever (19.4%) followed by dyspnea (14.9%) and the most common underlying disease was hypertension (37%). Pneumonia was the most common infectious disease (23.4%) followed by Spiss (15.7%). a total of 117(47.2%) patients had a previous history of hospitalization. Conclusion: The most common infectious diseases leading to hospitalization and death in the elderly arepneumonia and sepsis.